PERSPECTIVE APPROACH TO PSYCHO-SOMATIC DISORDERS IN ELDERLY PATIENTS WITH CERTAIN MEDICINAL PLANTS IN COVID PANDEMIC - Debashree Priyadarshini; Binodini Tripathy; Gopal C Nanda (International Journal of Ayurveda and Pharma Research, 2020)
Psychosomatic disorders have now become a common disease in present global scenario due to Covid pandemic. People are always in panic due to morbidity of the disease whereas the livelihood has become a secondary morbid condition due to economic slowdown. Under the above global scenario almost every person is undergoing certain psychosomatic problems either one or both of the factors. Apart from this, the present trend of competitive and conservative life-style has made young and old person to panic mental situations. The egoistic attitude of the human being and his inability to compromise his desire/demands tends to imbalance of temperament resulting into essential hypertension, insomnia, irritability etc. Ultimately such person becomes addicted to anxiolytic, anti-depressant and tranquilising drugs of modern medicine. Psychiatric disorders are commonly encountered by clinical medicine and the management includes psychotherapy, behavioural therapy, physical treatment with antipsychotic drugs, but the post management leads to addiction or drug dependence along with morbid withdrawal symptoms in patients. In view of problems of dependence specific approach of Ayurvedic concept like Satwavajaya and Daivavyapasraya have provided the light of protection but the practices are still limited due to orthodox beliefs. Some psychotropic drugs like Medhyarasayana etc. in single and compound form are described in classical texts for the management of different mental disorders. The use of herbs to offset these antecedents and outcome has greatly increased in recent years. Not only it is helpful for psychosomatic issues rather it would be helpful at least in such Covid pandemic as because the anti-psychotic drugs are scarce in market due to heavy personal demands. Ayurvedic approach can also create a trend of revitalising herbal preparations keeping behind the hazardous post drug complication. It is an attempt for mainstreaming the Ayurveda in present scenario.